Seismic moment tensor and focal mechanism for earthquake of February 22, 2024 in eastern Slovakia (12:54:15 UTC, 21.75E°E, 49.03°N, depth 9 km, ML3.0) - Д.В. Малицький; Л. Фойтікова; Я. Малек; О.А. Асташкіна; А.Р. Гнип; М.С. Добушовський; Р.М. Пак; М.О. Мельник; В.Г. Нікулін; В.В. Ігнатишин (Геофизический журнал, 2025)
The accuracy of the focal mechanism solution can depend very significantly on the number of stations used, especially in the case of weak earthquakes and sparse networks. We describe the procedure for retrieving the seismic moment tensor for the earthquake of February 22, 2024, which happened in Eastern Slovakia, using a limited number of seismic stations. We use records from only two stations of the Slovakian network: sk19 (49.25 °N, 21.93 °E) and sk20 (49.21 °N, 21.61 °E). The moment tensor inversion of high-frequency seismogram data in this study is based on a point source approach using the matrix method for the direct waves. The process involves generating records in displacements using the frequency and wave-number integration technique for an elastic horizontally layered medium. A method is presented for moment tensor inversion of only direct P- and S-waves, which is less sensitive to path effects modelling than reflected and converted waves, significantly improving the method’s accuracy and reliability. The location and origin time of the event are considered known. Based on forward modelling, a numerical technique is developed for the inversion of observed waveforms for the of moment tensor M(t) components obtained by generalized inversion.